2014
DOI: 10.1186/1745-6215-15-271
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind, placebo-controlled intervention trial of 3 and 10 mg sublingual melatonin for post-concussion syndrome in youths (PLAYGAME): study protocol for a randomized controlled trial

Abstract: BackgroundBy the age of sixteen, one in five children will sustain a mild traumatic brain injury also known as concussion. Our research found that one in seven school children with mild traumatic brain injury suffer post-concussion syndrome symptoms for three months or longer. Post-concussion syndrome is associated with significant disability in the child and his/her family and yet there are no evidence-based medical treatments available. Melatonin has several potential mechanisms of action that could be usefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 135 publications
0
16
0
Order By: Relevance
“…Ponsford et al showed long-term deficiency of sleep patterns associated with fatigue in TBI patients ( 6 ). To this end, a clinical trial is currently underway wherein children suffering from post-concussion syndrome receive sublingual melatonin for a month post-event ( 25 ) in an attempt to reduce symptoms following TBI. It might be that the degree of TBI impacts particularly on the circadian rhythm, though this remains speculation at this point in time.…”
Section: Discussionmentioning
confidence: 99%
“…Ponsford et al showed long-term deficiency of sleep patterns associated with fatigue in TBI patients ( 6 ). To this end, a clinical trial is currently underway wherein children suffering from post-concussion syndrome receive sublingual melatonin for a month post-event ( 25 ) in an attempt to reduce symptoms following TBI. It might be that the degree of TBI impacts particularly on the circadian rhythm, though this remains speculation at this point in time.…”
Section: Discussionmentioning
confidence: 99%
“…We included 132 children with a confirmed diagnosis of mTBI: 99 children had PPCS at 4 to 6 weeks post-injury (henceforth referred as 1-month post-injury) and 33 children who had mTBI at 1-month post-injury but had recovered. We recruited a convenience sample provided by a sub-study of a clinical trial investigating the efficacy of melatonin in PPCS (PlayGame Trial: NCT01874847), conducted at the Alberta Children's Hospital 24 . The current study aimed to identify neuroimaging biomarkers of recovery in children following mTBI.…”
Section: Subjectsmentioning
confidence: 99%
“…headache, confusion, vomiting, amnesia, balance problems etc.) and documented by emergency department medical personnel [19][20][21][22] . Concussion is considered to be part of the spectrum of mTBI 23 .…”
Section: Methodsmentioning
confidence: 99%